ANALYSIS OF FACTORS AFFECTING PRODUCTION AND THE LEVEL OF TECHNICAL EFFICIENCY OF CLOVE FARMING IN JAWAPOGO VILLAGE, MAUPONGGO DISTRICT, NAGEKEO REGENCY - Loy, Martinus Adrian; Suek, Johanna; Darlen, Maria Fransiska (Undana Press, 2024)
Cloves are one of the suitable commodities in Nagakeo Regency, but data from the last five years shows that clove productivity tends to decline. The decline in productivity is thought to be due to inefficient use of production factors. This study was conducted to answer research questions related to the technical efficiency of production factors. The study was conducted in Jawapogo Village, Mauponggo District, Nagekeo Regency. The location was determined deliberately with the consideration that Jawapogo village is one of the clove producing villages in Nagakeo Regency. This research involved 41 farmers who were taken randomly from households that had cloves. Data analysis was carried out descriptively and quantitatively. Quantitative analysis used Cobb-Douglas analysis and Technical Efficiency. Technical efficiency calculations are used by Frontier software. 4.1C. The results of the simultaneous regression analysis of the production factors included in the model have a significant effect on clove production. Meanwhile, partially the variable number of productive plants has a significant effect on clove production. Meanwhile, the variables of land area, plant age and labor did not have a significant effect. Meanwhile, the average technical efficiency is 0.50, so it is concluded that the use of production factors is not efficient. Inefficiency in clove farming is influenced by non-formal education and the age of the farmer. On the other hand, formal education has no significant effect. Therefore, increasing non-formal education through clove farming extension or training is needed to reduce technical inefficiencies in clove farming management.